Relações dialógicas no processo de educomunicação : análise em uma rede social na internet - Silva, Danilo Fonseca (2015)
Internet Social networks are embedded in time and academic spaces, setting up, if properly incorporated into the educational processes, as possible alternatives to dialogical interactions to the knowledge construction process. Do teachers and students meetings and interaction, in a social network on the Internet, as part of an educommunicative process, provide dialogical relations that contribute to the free construction of knowledge and reframing of these subjects? Taking into account this issue, this dissertation sought, as the main objective, to investigate and analyze the dialogical process between subjects, specially students and teachers who experience the academic world on a social networking site, taking part in a Facebook group created to provide supplementary educational activities. Besides that, this academic research specifically aimed at investigating and analyzing the dialogic process and educommunication concepts in an educational project context. It also aimed (i) to verify and analyze the possible Facebook contributions as a social networking site in the formation process, (ii) to observe the involved subjects manifestations and the possibilities for critical and collective knowledge construction; and (iii) contribute to fields of knowledge in an area where studies still show up to be quite incipient. In order to have these aims achieved, interdisciplinary literature surveys were undertaken over the area of educommunication, especially based on Soares (2011) and Schaun (2002), as well as about interactions and dialogues on the Internet social networks, supported by Recuero (2011 and 2012) and Primo (2011), both pervaded by Paulo Freire s reflections and texts (1987 and 2011). The adopted approach was qualitative and the methodological procedures were contemplated from the perspective of netnography, based essentially on Kozinets (2014) through virtual classroom observations plus focal interviews with Social Communication course professors and students - Journalism of the Federal University of Uberlândia (UFU), participants in a project with educommunicative purposes. Analyses showed broad dialogical effervescence, both in virtual and in physical environments, which enabled the joint construction of knowledge, beyond the borders of time, space and academic spaces provoking these subjects new perspectives of themselves and of the experienced social reality.